KUALITAS PENGUNGKAPAN LAPORAN KEBERLANJUTAN BERDASARKAN POJK NO. 51/ POJK.03/ 2017: PT SURYAMAS DUTA MAKMUR TBK TAHUN 2021-2022 - Sintong Mangandarmuda Harahap; Carmel Meiden (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
This study aims to analyze the quality of disclosure of sustainability reports based on POJK No. 51 / POJK.03 / 2017 in terms of economic, environmental and social aspects. This type of research is qualitative research, descriptive method at PT Suryamas Duta Makmur Tbk in 2021 and 2022. The results of this study indicate that PT Suryamas Duta Makmur Tbk has implemented POJK No. 51 / POJK.03 / 2017 in preparing a sustainable report, although not all aspects of POJK No.51 / POJK.03 / 2017 are disclosed. The disclosure of sustainable reports in 2021 and 2022 regarding economic aspects is fully met with very good quality with a disclosure score of 100%. Disclosure of environmental aspects in 2021 and 2022 has contributed good quality with a disclosure score of 62.5%. Disclosure of social aspects in 2021 and 2022 has a very good quality contribution with a disclosure score of 87.5%.